1881 Colo. Sess. Laws 856 - (:unkn) unknown (My University, 1881)
§ 1964: Prohibited the concealed carry of any pistol, Bowie-knife, dagger, or other deadly weapon. Violators punished by jail term no less than ten but not more than thirty days and fined not less than fifty but no more than one hundred dollars.
Keywords: CARRY - CONCEALED